Teachers’ responses to anxiety in students with autism spectrum disorder: Proposal of a predictive model - Hernández-González, Osvaldo; Spencer-Contreras, Rosario; de la Torre González, Belén; Rondón Mejías, Bárbara (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Students with autism spectrum disorder (ASD) experience clinical or subclinical levels of anxiety which problematizes the possibilities of communication and social interaction. Current educational demands require the exploration of variables linked to the mediation of teachers’ responses to the anxiety of students with ASD. Objective. To propose a predictive model based on mediating variables of teachers’ responses to the anxiety of students with ASD in inclusive schools. Methods. This manuscript is focused on the review of the variables: knowledge about ASD, emotional regulation strategies, experience in special/inclusive education, and teachers’ attitudes towards inclusion. Results. The evidence suggests that the variables reviewed are key in the responses of teachers to the anxiety of students with ASD. Based on this finding, a model is proposed that associates high knowledge about ASD, cognitive reassessment as a strategy for emotional regulation, positive attitude, and experience in special and/or inclusive education with responses from teachers that promote autonomy, while indicators such as low knowledge about students with ASD, expressive suppression as an emotional regulation strategy, negative attitude, and little experience in special and/or inclusive education are related to responses that problematize anxiety symptoms in students with ASD. Conclusion. The predictive model proposed here is speculative, but theoretically, it paves the way for possible empirical studies that demonstrate its validity.
Keywords: autism; anxiety; teacher’s attitude; inclusion; predictive model